Behavioral Economics: A Tutorial for Behavior Analysts in Practice (R. Freitas- Lemos & F. S. Oda, Trad.) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
In recent years, behavioral economics has gained much attention in psychology and public policy. Despite increased interest and continued basic experimental studies, the application of behavioral economics to therapeutic settings remains relatively sparse. Using examples from both basic and applied studies, we provide an overview of the principles comprising behavioral economic perspectives and discuss implications for behavior analysts in practice. A call for further translational research is provided.
Keywords: behavioral economics; demand; discounting; tutorial